We are not free - Chee, Traci (Houghton Mifflin Harcourt, 2020)
For fourteen-year-old budding artist Minoru Ito, her two brothers, her friends, and the other members of the Japanese-American community in southern California, the three months since Pearl Harbor was attacked have become a waking nightmare: attacked, spat on, and abused with no way to retaliate--and now things are about to get worse, their lives forever changed by the mass incarcerations in the relocation camps.